From Attire to Assault: Clothing, Objectification, and De-humanization – A Possible Prelude to Sexual Violence? - Awasthi, Bhuvanesh (Frontiers in Psychology, 2017)
In the context of objectification and violence, little attention has been paid to the perception neuroscience of how the human brain perceives bodies and objectifies them. Various studies point to how external cues such as appearance and attire could play a key role in encouraging objectification, dehumanization and the denial of agency. Reviewing new experimental findings across several areas of research, it seems that common threads run through issues of clothing, sexual objectification, body perception, dehumanization and assault. Collating findings from several different lines of research, this article reviews additional evidence from cognitive and neural dynamics of person perception (body and face perception processes) that predict downstream social behavior. Specifically, new findings demonstrate cognitive processing of sexualized female bodies as object-like, a crucial aspect of dehumanized percept devoid of agency and personhood. Sexual violence is a consequence of a dehumanized perception of female bodies that aggressors acquire through their exposure and interpretation of objectified body images. Integrating these findings and identifying triggers for sexual violence may help develop remedial measures and inform law enforcement processes and policy makers alike.